HUBUNGAN TEKANAN DARAH DENGAN FUNGSI KOGNITIF PADA GERIATRI DI RSUD ULIN BANJARMASIN - Diva Aurellia Rosa; Pagan Pambudi; Ahmad Husairi; Muhammad Welly Dafif; Dona Marisa (Homeostasis, 2022)
One health problems that often occur in elderly is a decline in cognitive function. The brain needs oxygen and glucose reserves to work, if there is a blood vessel blockage, it can cause oxygen and glucose inadequacy which can reduce the work function of brain nerve cells. Hypertension is a medical condition of an elevated vascular blood pressure above normal limits. The purpose of this study was to analyze the relationship between blood pressure and cognitive function in the elderly at RSUD Ulin Banjarmasin. This study is an analytic observational study using a cross-sectional method with total of 32 elderly people were selected using a purposive sampling method. Data was analyzed by using Pearson. The average value systolic blood pressure was 152,2 ± 5,1 from secondary data of medical record, and the average value of cognitive function using the Mini Mental State Examination (MMSE) was 26,3 ± 1,0 with Pearson correlation test results obtained value of p = 0.594 and r = 0.098. These findings provide additional evidence that there is no relation between blood systolic pressure and cognitive function in the elderly in RSUD Ulin Banjarmasin